2021
DOI: 10.1038/s41598-021-83262-5
|View full text |Cite
|
Sign up to set email alerts
|

Movement behavior of a solitary large carnivore within a hotspot of human-wildlife conflicts in India

Abstract: With a rise in human induced changes to natural habitats, large predators are forced to share space and resources with people to coexist within multiple-use landscapes. Within such shared landscapes, co-occurrence of humans and predators often leads to human-carnivore conflicts and pose a substantial challenge for biodiversity conservation. To better elucidate large carnivore space use within a hotspot of human-wildlife conflicts, we used GPS data for leopards (N = 6) to identify behavioral states and document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Our regular visits to stations to switch out camera batteries and SD cards and to collect bear hair may have altered movements by bears on our study site, which may have affected encounter histories and estimates of p and φ . Previous studies have shown that human recreation altered spatio‐temporal patterns of habitat use by wildlife (Dertain et al, 2021; Doherty et al, 2021; Naha et al, 2021), including bears (Coleman et al, 2013; Naves et al, 2001). Compared to demographic studies that use capture‐collar data and require daily trap checks, the degree of landscape impact by our study design was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Our regular visits to stations to switch out camera batteries and SD cards and to collect bear hair may have altered movements by bears on our study site, which may have affected encounter histories and estimates of p and φ . Previous studies have shown that human recreation altered spatio‐temporal patterns of habitat use by wildlife (Dertain et al, 2021; Doherty et al, 2021; Naha et al, 2021), including bears (Coleman et al, 2013; Naves et al, 2001). Compared to demographic studies that use capture‐collar data and require daily trap checks, the degree of landscape impact by our study design was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…A2 B and C). However, swamp deer showed temporal segregation with human, a behavioural strategy observed in other herbivores in human-dominated landscapes (Gaynor et al, 2018; Wilson et al, 2020; Naha et al, 2021). More radio-collaring and information from other areas in this landscape can substantiate the patterns found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Four large carnivores, tigers (Panthera tigris), leopards (Panthera pardus), sloth bears (Melursus ursinus), and hyenas (Hyaena hyaena) that co-occur extensively across peninsular India exemplify such variations (Joshi et al, 2013;Chanchani et al, 2016;Majgaonkar et al, 2019;Thatte et al, 2020). Of these, both felines occur across a diverse array of habitats, from dense forests to more arid open woodlands and savannas where they occupy home-ranges from <10 to >2,000 km 2 (Simcharoen et al, 2008(Simcharoen et al, , 2014Grant, 2012;Chundawat et al, 2016;Hunter and Barrett, 2019;Naha et al, 2021). Though both felines achieve their highest densities in Protected Areas, they persist in many multi-use landscapes (Joshi et al, 2013;Chanchani et al, 2016;Karanth et al, 2020), including forests and agro-ecosystems, where the smaller leopard, with its wider dietary niche can sometimes occur at relatively high densities as well (Athreya et al, 2013;Stein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%